2020
DOI: 10.1021/acs.jpcc.0c06977
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer Charge Transfer Coupled with Acoustic Phonon in Organic/Inorganic van der Waals Stacked Heterostructures: Self-Assembled Pt(II) Complex on a PtSe2 Monolayer

Abstract: Interlayer charge-transfer (CT) excitons in heterostructures are of great importance because of their crucial roles in manipulating the device performance and many-body quantum behaviors. Nonetheless, enigmas arise in organic/inorganic heterointerfaces because localized excitons and inhomogeneity in organic materials hinder the interlayer CT processes. Here, we demonstrate that the interlayer CT excitons form in the new organic/inorganic heterostructure composed by the Pt(II) complex 4Me and monolayered transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Moreover, by replacing the py-fpm with fused py-fqz, the delocalization length of Pt­(py-fqz) 2 increases to N = 8.5 (∼3 nm) . In addition, the exciton binding energy of aggregated Pt­(II) complexes is around 0.26 eV, which indicates the formation of CT exciton. , Note that the binding energy of CT exciton is smaller than that (∼1 eV) of the Frenkel exciton, consistent with the occurrence of significant exciton delocalization. Interestingly, the emission wavelength seems to positively correlate with the delocalization length; that is, the longer the delocalization is, the more bathochromic is the emission wavelength.…”
Section: Evidence Of Significant Exciton Delocalization In Aggregated...mentioning
confidence: 68%
See 1 more Smart Citation
“…Moreover, by replacing the py-fpm with fused py-fqz, the delocalization length of Pt­(py-fqz) 2 increases to N = 8.5 (∼3 nm) . In addition, the exciton binding energy of aggregated Pt­(II) complexes is around 0.26 eV, which indicates the formation of CT exciton. , Note that the binding energy of CT exciton is smaller than that (∼1 eV) of the Frenkel exciton, consistent with the occurrence of significant exciton delocalization. Interestingly, the emission wavelength seems to positively correlate with the delocalization length; that is, the longer the delocalization is, the more bathochromic is the emission wavelength.…”
Section: Evidence Of Significant Exciton Delocalization In Aggregated...mentioning
confidence: 68%
“…Moreover, by replacing the py-fpm with fused py-fqz, the delocalization length of Pt(py-fqz) 2 increases to N = 8.5 (∼3 nm). 4 In addition, the exciton binding energy of aggregated Pt(II) complexes is around 0.26 eV, 34 which indicates the formation of CT exciton. 35,36 Note that the binding energy of CT exciton is smaller than that (∼1 eV) of the Frenkel exciton, 35 consistent with the occurrence of significant exciton delocalization.…”
Section: Evidence Of Significant Exciton Delocalization In Aggregated...mentioning
confidence: 99%
“…An intentionally designed heterostructure would excite novel interfacial vibrational patterns and rectify the coupling with charge carriers, thus effectively manipulating charge separation and recombination across the interface. 20,21 Recent work demonstrated that charge recombination in the MoSe 2 /WSe 2 heterostructure is promoted by the heat-driven intralayer shear and breathing modes in the low-frequency region. 22 Thus far, the understanding of the nonradiative scattering across a Z-scheme heterostructure for photocatalysis is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…7,14,15 Recently, due to rapid advances in materials science, VC in the solid phase has been investigated, and the impact of VC on optoelectronic devices has received considerable attention. [16][17][18][19][20][21][22][23][24][25] Several studies have proposed that VC may assist photoinduced charge separation in photovoltaic materials, 16,18,25,26 although the correlation between VC-assisted charge separation and device performance is still unknown. 17,27 Despite fundamental and technical difficulties, this emerging field has considerable potential and various unexplored topics.…”
mentioning
confidence: 99%